Sequential Explanatory Mixed Method Approach to Understanding the Impact of Digital Media on Media Relations and Audience Engagement - Ezurike, Nduneche (British Journal of Marketing Studies, 2024)
Digital media has disrupted the media landscape, enabling audiences to consume news and information through a variety of channels beyond traditional media outlets, such as social media, blogs, and podcasts. As a result of the diversity of information offered via digital media platforms, media practitioners have been able to appeal in different ways to members in the society to enhance relationships and actualize personal objectives. This study adopted a sequential explanatory mixed method approach to investigate the impact of digital media on media relations and audience engagement. Findings from the survey carried out on media professionals revealed that a significant majority of respondents frequently utilize digital media metrics, such as engagement rates, reach, and sentiment analysis to gauge the effectiveness of their media strategies. Also, respondents generally find these metrics effective in capturing meaningful insights into audience behaviour, with a considerable portion viewing them as highly effective tools. However, challenges such as data interpretation difficulties due to lack of training and the lack of standardized metrics across platforms were identified as obstacles in fully leveraging digital metrics. participants noted opportunities such as improved audience targeting, real-time performance insights, and enhanced campaign evaluation, highlighting the potential of digital metrics to refine strategies and increase engagement. Results from the interviews further highlighted opportunities, specifically in areas like improved audience targeting, real-time performance insights, and enhanced campaign evaluation, all of which contribute to more precise and adaptive media strategies. The study, among other things, recommended that media organizations should provide comprehensive training on data interpretation and analytics to equip media professionals with the necessary skills to analyze and utilize digital media metrics effectively.